The Impact of Self-compassion Program on Self-compassion, Subjective Well-being and Meaning of Life among Adolescents - Ferhat Kardaş; Rufeyde Utkan (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study ise examine whether the Self-Compassion-based psycho-education intervention study is effective on the self-compassion, well-being, meaning of life results of high school students. It an experimental design study. The research, sample consists of 28 high school students in Van province in Turkey; 14 of them constitute the treatment group, 14 constitute the control. In alignment with reserach objektives, pretest, posttest, and follow-up tests were applied to treatment, while a pretest-posttest were given to the other group. We collected the data by using Scale Short Form of Self-Compassion, Subjective, Well-Being Scale for Adolescents, Meaning, in Life Scale for Adolescents. The developed program was administred to the treatment group for six-week period, after which a post-test was conducted. A follow-up test were administered to experimental group participants one month after posttest. By using t-test for dependent and independent samples, two-way anova test for repeated measures, we analyzed the research data. We found that no significantly difference of pre-test results of self-compassion, well-being, meaning of life in terms of treatment-control groups. This is likely due to the similar characteristics of the members of both groups. After administring of pretest-post-test, we found that the mean scores for self-compassion and well-being treatmen and control groups demonstrated an increase. Additionally, a significant differentiation emerged between these scores. With regard to the meaning of life, although the both pretest-posttest means, of the participants in the, treatment and control groups increased, no significant differentiations were observed between these scores. While we found no significantly differentiation among the posttest and follow-up test results in self-compassion and well-being dimensions of the treatment group, a significant difference between the posttest and follow-up test scores in the meaning in life dimension were found. All these findings were discussed in various dimensions and some suggestions were presented accordingly.Key words: Self-compassion, well-being, meaning of life, adolescents